Cognitive speed and selective attention: Possible markers for overtraining - Nederhoff, E.; Lemmink, K. A. P. M.; Zwerver, H. J. (Book of Abstracts - 9th Annual Congress European College of Sport Science, July 3-6, 2004, Clermont-Ferrand, France, 2004)
The overtraining syndrome (OTS) is a problem in athletic training that has received a lot of attention by researchers. OTS is characterised by underperformance due to an imbalance between (training) stress and recovery. Since complete rest for several weeks or months is the only known cure, detecting OTS in an early stage is of utmost importance. Until recently, no golden marker for detecting OTS in an early stage has been established. Stress is an important factor in OTS. High levels of stress have been related to decreased cognitive functioning. Fatigue and mood disturbances are consistent symptoms of OTS. In consistence with these findings, OTS has been linked with clinical depression and with chronic fatigue syndrome (CFS). Both depression and CFS have been associated with decreased processing speed. Also, disturbances of the hypothalamic-pituitary-adrenocortical (HPA) axis have been suggested to play a role in OTS. Disturbances in the HPA axis too have been related to alterations in selective attention and information processing. This lead us to the hypothesis that cognitive functioning is a possible marker for OTS. The purpose of the present study was to investigate whether stress and/or recovery are related to cognitive speed selective attention in elite athletes. Methods Twenty-one Dutch national and international level heavyweight male rowers were tested during a sport medical examination during which a maximal exercise test was performed and blood was drawn. The rowers were on average 24.5 ± 2 years old, their average height was 196 ± 4.6 cm, their average weight was 91.8 ± 7.8 kg and their average maximal oxygen uptake was 6.2 ± 0.6 l/min. To measure the rowers` stress and recovery levels the Recovery-Stress Questionnaire for athletes (RESTQ-sport; Kellmann & Kallus, 2001) was administered. Two neuropsychological tests were administered: the Vienna Determination Test (DT), which measures reactive stress tolerance and the related reaction speed, and the finger pre-cueing reaction time task (FPT; Miller, 1982), which measures visual selective attention and the related reaction time. 18 Complete datasets were obtained. Results From the medical examination no indications for overtraining were found. Scores on the RESTQ-sport revealed no extreme scores on stress or recovery, although some of the rowers had scores that were out of the range of mean ± SD of the whole group. Scores on the non-specific stress scales `General Stress` and `Lack of Energy` were correlated with scores on the DT (.50 < r < .61, p < .05) in the expected direction (i.e. higher scores on `General Stress` were associated with longer reaction times). Shorter reaction times on the FPT were associated with higher scores on the non-specific recovery scales `Physical Recovery`, `General Well-Being` and `Sleep Quality` (-.47 < r < -.62, p < .05) and with lower scores on the sport-specific stress scale `Fitness/Injury` (r = .49, p < .05). Discussion/Conclusion Results of this study are promising. More recovery related activities were related to shorter reaction times whereas a higher frequency of stress was related to longer reaction times. This shows that neuropsychological tests might indeed be useful instruments with regard to OTS. If in future research changes in the stress-recovery balance are shown to lead to changes in performance on these neuropsychological tests, these tests might become an important tool in preventing OTS.